Preliminary Studies to Characterize the Temporal Variation of Micronutrient Composition of the Above Ground Organs of Maize and Correlated Uptake Rates - Martins, Karla Vilaça; Dourado-Neto, Durval; Reichardt, Klaus; de Jong van Lier, Quirijn; Favarin, José Laércio; Sartori, Felipe Fadel; Felisberto, Guilherme; Mello, Simone da Costa (Frontiers in Plant Science, 2017)
The improvement of agronomic practices and the use of high technology in field crops contributes for significant increases in maize productivity, and may have altered the dynamics of nutrient uptake and partition by the plant. Official recommendations for fertilizer applications to the maize crop in Brazil and in many countries are based on critical soil nutrient contents and are relatively outdated. Since the factors that interact in an agricultural production system are dynamic, mathematical modeling of the growth process turns out to be an appropriate tool for these studies. Agricultural modeling can expand our knowledge about the interactions prevailing in the soil-plant-atmosphere system. The objective of this study is to propose a methodology for characterizing the composition of different organs and extraction, distribution and export of micronutrients during maize plant development, based on modeling nutrient uptake, crop potential evapotranspiration and micronutrient partitioning in the plant, considering the micronutrient uptake rate in a given production system. This preliminary characterization study considers the temporal variation of the micronutrient uptake rate in the aboveground organs, which defines crop needs and the critical nutrient content of the soil solution. The methodology allowed verifying that, initially, the highest fraction of dry matter is assigned to the leaves. After the R1 growth stage, the largest part of dry matter is partitioned to the stalk, which in this growth stage is the main storage organ of the maize plant. During the reproductive phase, the highest fraction of dry matter is conferred to the reproductive organs, because after flowering there is intense demand for carbohydrates and micronutrients for grain filling. The micronutrient (B, Cu, Fe, Mn and Zn) content follows a power model, with higher values for the initial growth stages of development and levelling off to minimum values at the R6 growth stage. The maximum micronutrient absorption rates occur in the reproductive R4 and R5 growth stages, mainly. These evaluations allowed to predict the maximum micronutrients requirements, considered equal to respective stalk sap concentrations.